Mass spectral characterisation of a polar, esterified fraction of an organic extract of an oil sands process water - Rowland, S.; Pereira, A.; Martin, J.; Scarlett, Alan; West, C.; Lengger, S.; Wilde, M.; Pureveen, J.; Tegelaar, E.; Frank, R.; Hewitt, L. (2014)
Copyright © 2014 John Wiley & Sons, Ltd. RATIONALE Characterising complex mixtures of organic compounds in polar fractions of heavy petroleum is challenging, but is important for pollution studies and for exploration and production geochemistry. Oil sands process-affected water (OSPW) stored in large tailings ponds by Canadian oil sands industries contains such mixtures. METHODS A polar OSPW fraction was obtained by silver ion solid-phase extraction with methanol elution. This was examined by numerous methods, including electrospray ionisation (ESI) Fourier transform ion cyclotron resonance mass spectrometry (FTICRMS) and ultra-high-pressure liquid chromatography (uHPLC)/Orbitrap MS, in multiple ionisation and MS/MS modes. Compounds were also synthesised for comparison. RESULTS The major ESI ionisable compounds detected (+ion mode) were C15-28 SO3 species with 3-7 double bond equivalents (DBE) and C27-28 SO5 species with 5 DBE. ESI-MS/MS collision-induced losses were due to water, methanol, water plus methanol and water plus methyl formate, typical of methyl esters of hydroxy acids. Once the fraction was re-saponified, species originally detected by positive ion MS, could be detected only by negative ion MS, consistent with their assignment as sulphur-containing hydroxy carboxylic acids. The free acid of a keto dibenzothiophene alkanoic acid was added to an unesterified acid extract of OSPW in known concentrations as a putative internal standard, but attempted quantification in this way proved unreliable. CONCLUSIONS The results suggest the more polar acidic organic SO3 constituents of OSPW include C15-28S-containing, alicyclic and aromatic hydroxy carboxylic acids. SO5 species are possibly sulphone analogues of these. The origin of such compounds is probably via further biotransformation (hydroxylation) of the related S-containing carboxylic acids identified previously in a less polar OSPW fraction. The environmental risks, corrosivity and oil flow assurance effects should be easier to assess, given that partial structures are now known, although further identification is still needed.